An Application Of Sarāṇīyadhamma In the working of Business Network Management Staff, Kasikornthai Bank - Boonrungkiat, Punnapha (Journal of Dhamma for Life, 2023)
The objectives of this research were: 1) to study an application of Sarāṇīyadhamma in working of business network management staff, Kasikornthai Bank 2) to compare the application of Sarāṇīyadhamma in working of business network management staff, Kasikornthai Bank according to personal factors. 3) to study suggestions about the application Sarāṇīyadhamma in working of business network management staff, Kasikornthai Bank. The sample group consisted of 136 people. The tool used was a questionnaire. The statistics used to analyze the data were frequency, percentage, mean, standard deviation. T test and one-way ANOVA test. The mean differences were analyzed individually with the method of Scheffe (Post Hoc). The results of the study were found that: 1) An application of Sarāṇīyadhamma in working of business network management staff, Kasikornthai Bank, including 6 areas, is at a high level. 2) An application of Sarāṇīyadhamma in working of business network management staff, Kasikornthai Bank, there was no significant difference at the .05 level.